The Legal Aspect of External Governance Mechanisms in Public Joint Stock Companies: A Comparative Study - Masaadeh, Ahmed (Journal of Legal Studies and Researches, 2023)
Corporate governance is a more effective way to ensure that the financial and administrative aspects of public shareholding companies operate in accordance with legal, financial and administrative controls. In this study, we concluded that corporate governance is the only way out and the most powerful and effective solutions to come out with a guarantee of the rights of shareholders, investors, third parties, rights holders and creditors.